HUBUNGAN KONFORMITAS PEER GROUP DENGAN QUARTER LIFE CRISIS PADA MAHASISWA FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI JAKARTA - Alvi Alhafizh Syachri; Harry Handoko; Ivan Surya Pratama; Ramadon, Zaelani (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2022)
This research’s objective is to determine and examine the relationship between peer group conformity and quarter-life crisis in students of the Faculty of Social Sciences, State University of Jakarta. This research uses quantitative approach and purposive sampling technique with a sample of 100 students of the Faculty of Social Sciences, State University of Jakarta with the criteria of being 20 to 25 years old. The instruments used in this research are the conformity scale and the quarter-life crisis scale. The data were then analyzed using the Pearson product-moment correlation with P = 0.004 and r = 0.283, which means the hypothesis is accepted. This means that the higher the conformity score, the higher the quarter-life crisis experienced by the students of the Faculty of Social Sciences, State University of Jakarta, and vice versa.